THE CONCEPT OF MUSLIM’S TAQWA AND ISLAMIC PSYCHOLOGY MEASUREMENT - Ahmad Hidayat; Fikri Fikri; Novis Krisma (Psikoislamedia : Jurnal Psikologi, 2024)
"Taqwa" is a familiar term among Muslims, serving as a reminder to continuously enhance one's piety. It has also been incorporated into the national education goals in Indonesia, extending its implementation to the field of education and industry. This study aims to develop and measure the concept of taqwa. Employing a quantitative method and purposive sampling techniques, data collection utilized the Muslim Piety Scale (MPS), developed by the researcher based on Kuning's (2018) taqwa concept. The study involved 227 Muslim students from the Faculty of Psychology at the Islamic University of Riau (UIR). Data analysis was conducted using Smart PLS 3.0 software. Findings revealed that the taqwa construct's four dimensions had items reflecting each component of taqwa. The dimension of controlling anger made the most dominant contribution to the taqwa construct, followed by forgiveness, seeking forgiveness (istighfar), and generosity. The developed taqwa scale from this study can serve as a tool for measuring piety in educational and industrial settings, specifically for individuals of the Islamic faith.